TI_GERICHTE 60.2005.38 vom 15. Oktober 2007 , Istanza di indennità per ingiusto procedimento. accusato prosciolto - TI Tribunale d'appello (2007)
Istanza di indennità per ingiusto procedimento. accusato prosciolto